Theoretical exploration on structures, bonding aspects and molecular docking of α-aminophosphonate ligated copper complexes against SARS-CoV-2 proteases - Yadav, Oval; Kumar, Manjeet; Mittal, Himanshi; Yadav, Kiran; Seidel, Veronique; Ansari, Azaj (Frontiers in Pharmacology, 2022)
Recent years have witnessed a growing interest in the biological activity of metal complexes of α-aminophosphonates. Here for the first time, a detailed DFT study on five α-aminophosphonate ligated mononuclear/dinuclear CuII complexes is reported using the dispersion corrected density functional (B3LYP-D2) method. The electronic structures spin densities, FMO analysis, energetic description of spin states, and theoretical reactivity behaviour using molecular electrostatic potential (MEP) maps of all five species are reported. All possible spin states of the dinuclear species were computed and their ground state S values were determined along with the computation of their magnetic coupling constants. NBO analysis was also performed to provide details on stabilization energies. A molecular docking study was performed for the five complexes against two SARS-CoV-2 coronavirus protein targets (PDB ID: 6LU7 and 7T9K). The docking results indicated that the mononuclear species had a higher binding affinity for the targets compared to the dinuclear species. Among the species investigated, species I showed the highest binding affinity with the SARS-CoV-2 Omicron protease. NPA charge analysis showed that the heteroatoms of model species III had a more nucleophilic nature. A comparative study was performed to observe any variations and/or correlations in properties among all species.